Species diversity, distribution and abundance of puffers (family: tetraodontidae) occurring along the coast of Tamilnadu with special reference to biology and population dynamics of lagocephalus lunaris (bloch and schneider, 1801) - Swetha G. Ram (KUFOS, 2019)
Abstract- The diversity distribution and abundance of pufferfishes (Family Tetraodontidae ) along the Tamil Nadu coast along with the population dynamics and biology of Lagocephalus lunaris was analysed in the present study. The pufferfishes collected from four stations (Chennai, Tuticorin, Parangipettai and Kanyakumari) consisted of 14 species belonging to 5 different genera viz. Lagocephalus lunaris, L. inermis, L. spadiceus, L. scleratus, L. lagocephalus, Arothron hispidus, A. immaculatus, A. stellatus, A. reticularis, A.nigropunctatus, A. mappa, Chelonodon patoca, Torquigener brevipinnis and Takifugu oblongus. The various diversity indices were worked out as Margelef Species Richenss (d) 1.34, Shannon Diversity index (H’) 0.633 and Pielou’s eveness index (J’) 0.273, The Simpson dominance (λ) 0.041 and Simpson Dominance index (1-λ) 0.959. The growth parameters L∞ and K were 37.80cm and 0.76/year. t0 was found to be -0.093. The VBGF equation was derived as Lt = 37.8 (1 – e –0.76 (t – (-0.093))). The natural mortality, total mortality and fishing mortality was found to be 1.34/yr, 1.397/yr and .06/yr. Crustaceans were the major food item, followed by fishes and cephalopods. The overall sex ratio was recorded to be 1: 1.38. The size at first maturity in males and females were 15.1 cm and 14.8 cm respectively. The species exhibited fractional spawning with two spawning peaks one in June – July and other in September – December. This was also supported by the higher gonadosomatic index values in these months. Length – weight relationship of male, female and pooled data was W = 0.035 x L2.749 (r2 = 0.961), W = 0.032 x L2.818 (r2 = 0.967) and W = 0.031 x L2.810 (r2 = 0.966) respectively. The species exhibited isometric growth.